2020
DOI: 10.1002/eat.23237
|View full text |Cite
|
Sign up to set email alerts
|

Between wellness, relapse, and remission: Stages of illness in anorexia nervosa

Abstract: ObjectivePsychiatric illnesses, like medical illnesses, can sometimes be considered as progressing through stages. Understanding these stages can lead to a better understanding of pathophysiology, and clarification of prognosis and treatment needs. Opinions from experts in the field of anorexia nervosa (AN) were sought to create a model of stages of illness.MethodThe Delphi approach was used to achieve consensus from a panel of 31 individuals from a range of disciplines with expertise in AN. Over three iterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Further, illness progression is thought to be linked to changes in underlying pathophysiology, which could be better quantified by biomarkers. There has been growing interest in applying a staging model for AN [ 106 ] to represent different stages of the disorder from acutely ill to fully recovered. However, while experts reached, for example, consensus on a five-stage model in AN, there is still little agreement regarding appropriate biomarkers (besides BMI) that could be used to differentiate these stages of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Further, illness progression is thought to be linked to changes in underlying pathophysiology, which could be better quantified by biomarkers. There has been growing interest in applying a staging model for AN [ 106 ] to represent different stages of the disorder from acutely ill to fully recovered. However, while experts reached, for example, consensus on a five-stage model in AN, there is still little agreement regarding appropriate biomarkers (besides BMI) that could be used to differentiate these stages of illness.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting data over the involvement of excessive and maladaptive habits in eating disorders (25,47). Using a self-reported habit index, Davis et al recently found that the chronicity and severity of anorexia nervosa were related to the strength of habits (48).…”
Section: Discussionmentioning
confidence: 99%
“…A BMI of 18.5 kg/ m 2 is the suggested lower threshold of normal BMI in the general population, and is commonly used as a guide for "underweight" status in meeting criteria for AN [59]. There is some consensus within the eating disorders field that achieving BMI ≥ 18.5 kg/m 2 is a required component of remission [72], and several studies support that this threshold is associated with sustained recovery [25,73,74]. In our sample, the rate of maintenance at or above a BMI of 18.5 kg/m 2 for the duration of follow-up, from one to five years, was 46.1%, similar to or slightly higher than rates reported in previous studies [12,24,41].…”
Section: Discussionmentioning
confidence: 99%